Perioperative optimization, enhanced recovery and fast-track programs: why are they booming? What are these programs actually and how are they implemented into practice? - Mc Loughlin, Santiago; Fraidenraij, Uriel; Álvarez, Adrián O. (Revista Argentina de Cirugía, 2021)
From 2015 to date, the authors of this review have implemented several enhanced recovery periope- rative programs in Latin America. In the following article, we present a general introduction to the con- cepts of perioperative optimization and summarize our experience working in the region. Throughout this review, readers will also find the three fundamental elements of perioperative optimization. First, the creation and roles of a perioperative team. Second, the systematic and standardized registration of the surgical practice and its outcomes. And finally, the description of the continuous improvement cycle as a working method for adjusting daily practice based on the analysis of one’s own data.